Out there: Whare and Fale performing abroad - Engels-Schwarzpaul, A.-Chr. (University of Queensland Press, 2009)
What was once classed as 'savage ornament', which could not possibly register as architecture, has today morphed into the stuff of 'iconic architecture'. From another perspective, what began as a whare tupuna or a fale tele has sometimes turned into curios, for a time only or for ever. Along with the changes in status, these houses also changed their performative roles. This paper briefly traces the journeys abroad of Māori whare and Samoan fale, in the nineteenth and early twentieth centuries, which were designed for purposes other than that of their destinations, and some fale and whare that were designed to travel abroad in the 1960s and early 2000s. The houses in the former group often travelled with an accompanying expectation: that relationships would be performed and fulfilled. In the latter case, this expectation seems to have been replaced with more instrumental ones. But on the websites promoting them, relationships still feature as important parts of their essence and performance. This paper explores similarities and differences in the representation and performance of Māori and Samoan architecture and culture overseas, with respect to notions of relationships, visibility, agency, and interpretation.